Original paperFavourable impact of acute myocardial infarction treatment by percutaneous coronary intervention on cardiovascular efficiency during one-year observation - Pawłowska-Jenerowicz, Wiesława; Lechowicz, Waldemar; Dąbrowski, Marek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2006)
Background: Progress in managing myocardial infarction (MI) is improving survival but is also increasing the number of patients with heart failure. Early reperfusion is considered the best method of preventing post-myocardial infarction left-ventricular dysfunction. Aim: To determine whether treatment of acute myocardial infarction by percutaneous coronary intervention (PCI) results in significantly better long-term cardiovascular efficiency in comparison with conservative treatment. Methods: One hundred patients with myocardial infarction, 50 of whom were treated conservatively (group I) and 50 by PCI (group II) in the acute period were enrolled in the study. After 3, 6 and 12 months, spiroergometric tests were performed in all of the patients. Results: Group II showed superior spiroergometric parameters throughout the period of observation. In group I these results gradually showed significant improvement, but after one year they remained at a worse level (MET: 5.7 vs 6.1; p<0.02, VE/VCO 2 : 33.3 vs 31; p<0.02, VE-VCO 2 : 27.1 vs 24.5; p<0.01) and some of them did not reach the PCI group’s initial level (p<0.02 for MET, and p<0.01 for VE-VCO 2 index). Conclusions: PCI patients are characterized by better cardiovascular efficiency already at 3 months post-MI, and do not improve significantly during one year of follow-up. Conservatively treated patients are characterized by significant progressive improvement in cardiovascular efficiency parameters; however, one year after MI cardiovascular efficiency in this group is inferior to that in PCI patients. Analysis of expired CO 2 and assessment of exercise ventilation parameters (VE/VCO 2 , and VE-VCO 2 index) give a more accurate assessment of cardiovascular efficiency than peak oxygen consumption (peak VO 2 ).